(untitled) (Journal of Computational Mathematics, 1994)
A necessary and sufficient condition of regularity of (0,1,…,m-2,m) interpolation on the zeros of Laguerre polynomials L_n^(α)(x) (α≥-1) in a manageable form is established. Meanwhile, the explicit representation of the fundamental polynomials, when they exist, is given. Moreover, it is shown that, if the problem of (0,1,…,m-2,m) interpolation has an infinity of solutions, then the general form of the solutions is f_0(x)+Cf_1(x) with an arbitrary constant C.